Use of Suture tightening automated device COR-KNOT® for minimally invasive heart valve surgery: Our initial experience in Bangladesh - Sazzad, Md Faizus; Ghafoor, Nusrat; Roy, Siba Pada; Munshi, Swati; Khanam, Feroza; Chanda, Prasanta Kumar; Wadud, Armane; Islam, Sirajul; Ahmed, Farooque; Siraj, Masoom; Kah, Ti Lian; Kofidis, Theodoros (Bangladesh Heart Journal, 2019)
Background: COR-KNOT® (LSI Solutions, New York, NY, USA) is an automated suture securing device has not been well known. We report a case series for first automated knotting device used for minimally invasive heart valve surgery in Bangladesh. Method and Results: To overcome the challenge of knot securing via a Key-Hole surgery we have used CORKNOT ®. The newest device is capable of remotely and automatically secure sutures and simultaneously can cut and remove the excess suture tails. We covered the spectrum of heart valve surgery: There was one case of bioprosthetic aortic valve replacement, one case of mitral valve repair, one case of bioprosthetic mitral valve replacement, one case of failed mitral valve repair with COR-KNOT® explantation followed by mechanical mitral valve replacement and one case of redo-mitral valve replacement. Average length of hospital stays was 5 ± 1days. There was one reopening, one post-operative atrial fibrillation. No wound infection and no 30day mortality. Conclusion: We conclude, COR-KNOT® is a safe and effective tool to reduce the duration of operation. Clinical outcome of heart valve surgery with COR-KNOT® is comparable with other methods of suture tying methods. Bangladesh Heart Journal 2019; 34(2) : 127-131